2002
DOI: 10.1038/sj/mp/4000919
|View full text |Cite
|
Sign up to set email alerts
|

Preferential transmission of interleukin-1 receptor antagonist alleles in attention deficit hyperactivity disorder

Abstract: Keywords: attention deficit hyperactivity disorder; ADHD; interleukin-1 receptor antagonist gene; transmission disequilibrium test

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…Allele 2 of the IL1RN VNTR has been associated with type 1 diabetes mellitus, lichen sclerosus, psoriasis, ulcerative colitis, systemic lupus erythematosus, diabetic nephropathy, multiple sclerosis, osteoporotic fractures, essential hypertension, attention deficit hyperactivity disorder, and alopecia areata, as well as survival following severe sepsis (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Polymorphisms within IL1B…”
Section: Maksymowych Et Almentioning
confidence: 99%
“…Allele 2 of the IL1RN VNTR has been associated with type 1 diabetes mellitus, lichen sclerosus, psoriasis, ulcerative colitis, systemic lupus erythematosus, diabetic nephropathy, multiple sclerosis, osteoporotic fractures, essential hypertension, attention deficit hyperactivity disorder, and alopecia areata, as well as survival following severe sepsis (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Polymorphisms within IL1B…”
Section: Maksymowych Et Almentioning
confidence: 99%
“…Elevated levels of proinflammatory cytokines such as interleukin-1beta (IL-1β), interleukin-6 (IL-6), tumor necrosis-factor alpha (TNF-α) and interferon-gamma (IFN-γ) have been observed in adult-onset neuropsychiatric disorders such as schizophrenia [4, 5], bipolar disorder [6, 7] and major depression [8, 9]. These proinflammatory cytokines have also been indicated to have a role in childhood neuropsychiatric disorders such as autism [10, 11] and ADHD [12]. In addition, recent studies have indicated that antipsychotics and antidepressants suppress the proinflammatory cytokines and increase the levels of anti-inflammatory cytokines [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Tested genes have included DRD4, COMT, HTR2A, DAT1, dopamine beta-hydroxylase, dopa decarboxylase, CHRNA7, and interleukin 1, among others. [8][9][10][11][12][13][14][15][16] DRD4 is of interest as a candidate gene as it codes for a 7-transmembrane G-proteincoupled dopamine receptor, which is a member of the D2-like dopamine receptor family. DRD4 is expressed in regions implicated in ADHD [17][18][19] including the limbic system, frontal cortex, and globus pallidus.…”
Section: Introductionmentioning
confidence: 99%